Essential English for journalists, editors and writers - Evans, Harold Matthew, Sir, 1928-2020 (London : Pimlico, 2000)
This brisk and pungent guide to the use of words as tools of communication is written primarily for journalists, yet its lessons are of immense value to all who face the problem of giving information, whether to the general public or within business, professional or social organizations. What makes a good English sentence? How should you rewrite a bad one? What clichés and other word-traps are to be avoided? Using a wealth of examples drawn from British and American newspapers, Essential English is an indispensable guide for all who have to convey information by the written or printed word.
Keywords: Engels ; journalistiek